2012
DOI: 10.1186/1471-2490-12-28
|View full text |Cite
|
Sign up to set email alerts
|

Minimal percentage of dose received by 90% of the urethra (%UD90) is the most significant predictor of PSA bounce in patients who underwent low-dose-rate brachytherapy (LDR-brachytherapy) for prostate cancer

Abstract: BackgroundTo clarify the significant clinicopathological and postdosimetric parameters to predict PSA bounce in patients who underwent low-dose-rate brachytherapy (LDR-brachytherapy) for prostate cancer.MethodsWe studied 200 consecutive patients who received LDR-brachytherapy between July 2004 and November 2008. Of them, 137 patients did not receive neoadjuvant or adjuvant androgen deprivation therapy. One hundred and forty-two patients were treated with LDR-brachytherapy alone, and 58 were treated with LDR-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…There have been several reports to compare the treatment outcomes and GU or GI toxicities [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, they included a variety of LDR-BT modalities or sources, or different prescribed doses such as mixed 125 I and 103 Pb [ 8 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports to compare the treatment outcomes and GU or GI toxicities [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, they included a variety of LDR-BT modalities or sources, or different prescribed doses such as mixed 125 I and 103 Pb [ 8 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stones et al . reported, even at a high grade, if the tumor was confined to the prostate gland, BT only is adaptive, but there are also reports with opposite results [ 9 , 10 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with a recent publication that analyzed the clinicopathological and post-dosimetric parameters predictors of PSA bounce. In that report, no patient with PSA bounce after low-dose rate brachytherapy experienced biochemical recurrence, while 10/150 patients that did not meet the criteria for bounce were diagnosed with biochemical recurrence [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the suspected association between bounce phenomenon and bDFS. Other authors have suggested that inflammatory processes or a greater prostate size cause higher PSA secretion from the residual healthy prostate [18]. These theories, however, fail to explain the correlation between PSA bounce and bDFS.…”
Section: Discussionmentioning
confidence: 71%